Teachers' Satisfaction with Salary in Accredited and Non- Accredited Community Campuses of Pokhara Metropolis - Bhandari, Narayan Prasad (Academia Journal of Humanities & Social Sciences, 2024)
Higher education plays a significant role in achieving sustainable development goals. In Nepal’s case, sustainability of higher education roots to the academic as well as institutional quality, which demands for the satisfaction of manpower working in the concerned institutions. This study has been conducted in Pokhara Metropolis and attempts to identify the satisfaction status of teachers in accredited and non-accredited campuses with the following objectives: 1) to identify the variation in salary status of teachers among accredited and non-accredited community campuses and 2) to examine the satisfaction level of teachers over the current salary packages. The present study adopted quantitative research design, administrating online based survey questionnaire for data collection and testing mean values to compare and contrast the satisfaction. This study has found that teachers of study area are not satisfied with the salary offered by the campuses. Furthermore, teachers of accredited campuses are more dissatisfied as compared to the teachers of non-accredited campuses. It also identifies that there is a variance in salary packages between two types of campuses. Finally, it is concluded that both campuses are required to explore and apply appropriate policies to increase the salary satisfaction of teachers.